An assessment of the performance of the lead program in selected barangays of Ormoc Bay, Leyte - Tabinas, Mario B. (Iloilo City University of the Philippines in the Visayas)
This study aimed to determine the effects of the Livelihood Enhancement for Agricultural Devellopment (LEAD) Program on the lives of the targeted beneficiaries in the selected coastal barangays of Ormoc Bay in Leyte. The LEAD Program is a continuing program of the Department of Agriculture-National Agriculture and Fishery Council (DA-NAFC) that aims to increase the income of the beneficiaries. The program's main agenda is to empower marginalized farmers and fishermen organizations and enable them to participate in mainstream agricultural, processes and enhance their entrepreneurial skills (NAFC Quarterly, 2003). The three LEAD prponents' included in this study are : Wanga Fisherfolk Association (WAFO, Naungan Fishermen's Association (NAFO), and Ormoc YMCA Fishermen's Association (OYFA). The result of this study revealed that the LEAD program have paved the way for the beneficiaries i order to acquire material, technical and financial support services for their socio-economic upliftment.. These undertakings have significantly contributed to their development and helped facilitate their livelihood activities. The LEAD projects also served as initiator and catalyzer, as they strived to attain cohesiveness in their group and at the same time meet their desire to improve their socio-economic conditions. Generally hte results of the study revealed that the LEAD Program have made considerable impact on the lives of the beneficiaries, particularly in the increase of the levels of income and increasing membership in their respective organizations. With the full implementatio of the Local Government Code, where agricultural servces is developed to the LGU'S, there is a need to further intensify the implementation of the LEAD program to the marginal sector, based on the principles of local autonomy. Castle (1977) in his study, points out that local autonomy is the very heart of rural development. this principle would accelerate the program's beneficial effects towards harnessing the broad based participation of farmers and fisherfolks and at the same time reap the net benefits of a modernized agriculture and fisheries sectors for the country's marginalized sector. this would strenghten the organizational and financial capacity of LEAD beneficiaries, to actively engage in local development activities that affect their klives.
Research Paper (Management 299) -- U. P. in the Visayas, November 2005.